Pastoral household's perceptions of non pastoral activities in Yabello district, Oromia region, Ethiopia - Doyo Kena (Cogent Economics & Finance, 2021)
The study examined the pastoralists' perception towards non-pastoral activities and the proportion of pastoralist income from diverse livelihood activities in the pastoral areas of the Yabello district. Data were obtained from a survey of 180 household heads selected using a simple random sampling technique. Key informant interviews and focus group discussions were undertaken to gather data having qualitative nature. Descriptive and inferential analyses were used to analyze the data. The result shows that livestock rearing and crop production (72.49%) were the major sources of income for the respondents. A greater proportion (40% i.e. cumulative percentages of those who agree and strongly agree) of the household support that crop cultivation is as important as livestock rearing. Greater proportions (88.8%) of pastoral households also support that, practicing non-pastoral non-farm activities reduces climate-related risks, and the majority support undertaking diverse activities than relying on a single income source. The results also indicated that younger household heads, households with larger family sizes and lower livestock holding, and closer to the nearest market had positive perceptions towards non-pastoral activities. Pastoralist perception towards non-pastoral activities is gaining positive pattern and thus indicating the need for policy and development practice in line with their choice and ensuring sustainable livelihood.
Keywords: 330; Non-pastoral activities; Pastoralist; Perception